Biological validation of feline serum cystatin C: The effect of breed, age and sex and establishment of a reference interval. Issue 2 (May 2015) - Ghys, L.F.E.; Paepe, D.; Duchateau, L.; Taffin, E.R.L.; Marynissen, S.; Delanghe, J.; Daminet, S.
Highlights: This is the first large-scale study to determine the effect of age, sex and breed on feline sCysC and establishment of an RI. A promising result is that there was no biological variation observed for sCysC compared to sCr. Now, further studies are necessary to evaluate if sCysC is more sensitive and specific to detect a decreased GFR. Healthy cats and cats with CKD need to be studied and their GFR needs to be correlated with their sCysC concentration. Abstract: Chronic kidney disease (CKD) is common in cats, but the routine renal markers, serum creatinine (sCr) and urea, are not sensitive or specific enough to detect early CKD. Serum cystatin C (sCysC) has advantages over sCr, both in humans and dogs, and sCysC concentration is significantly higher in cats with CKD than in healthy cats. The objective of this study was to determine the effect of age, sex and breed on feline sCysC and to establish a reference interval for feline sCysC. In total, 130 healthy cats aged 1–16 years were included. sCysC was determined using a validated particle-enhanced nephelometric immunoassay. sCr, urea, urine specific gravity, urinary protein:creatinine ratio (UPC) and systolic blood pressure (SBP) were also measured. No significant differences in sCysC concentration were observed among young, middle-aged and geriatric cats, female intact, female neutered cats, male intact and male neutered cats, or among purebred and domestic short-or longhaired cats. The 95% reference interval for feline sCysC was determined to be 0.58–1.95 mg/L. sCr was significantly higher in geriatric cats than young cats. Serum urea in geriatric cats was significantly higher than in middle-aged and young cats ( P  = 0.004 and P  <   0.001, respectively). SBP in geriatric cats was significantly higher than in both middle-aged and young cats ( P  = 0.004 and P  = 0.040, respectively). Male neutered and female neutered cats had significantly higher serum urea concentrations than female intact cats ( P  = 0.003 and P  = 0.006, respectively). Male intact cats had a significantly higher UPC than female intact and female neutered cats ( P  = 0.02 for each comparison). There were no significant differences among sex groups for USG. It is of concern that sCysC in the majority of cats with CKD in previous studies falls within the reference interval calculated in this study. Further studies are warranted to evaluate the diagnostic value of sCysC as a renal marker in cats.